VD_FINDINFO Décision / 2013 / 509 vom 4. Juni 2013 - VD Tribunal cantonal (2013)
CLASSEMENT DE LA PROCÉDURE, PREUVE DE LA VÉRITÉ, DIFFAMATION | 319 al. 1 CPP (CH), 319 CPP (CH), 322 al. 2 CPP (CH), 385 CPP (CH)